PERFORMANCE OF THIN-TAILED SHEEP AS SACRIFICIAL LIVESTOCK SOLD BY SEASONAL TRADERS IN SLEMAN - Ariyanti, Febri; Kristanti, Miftah Amalia; Halomoan, Igor Anggoro; Prihanani, Nur Ika; Hidayah, Nurulia (Buletin Veteriner Udayana, 2025)
The Eid al-Adha celebration is a major annual event that offers substantial economic opportunities for seasonal livestock traders. Among the various types of sacrificial livestock offered, thin-tailed sheep (TTS) are commonly sold. This study aimed to evaluate the production performance of TTS marketed by seasonal traders. A total of 153 TTS aged 1-1.5 years (U1) and 1.5-2.5 years (U2) were sampled from three seasonal livestock trading locations in Sleman. All animals were confirmed to be healthy and free from physical defects. Data collection included both measurement and observations, focusing on production performance indicators such as body weight, body condition score (BCS), and linear body measurements (height at withers, chest circumference, body length, scrotal circumference), along with exterior characteristics (body colour, horns presence, and eye circumference). Quantitative data were analyzed using ANOVA in SPSS version 28, while qualitative data were analyzed descriptively. The results indicated that TTS sold by seasonal traders met the basic requirement for sacrificial livestock in terms of age and condition. Significant differences (P<0.05) between U1 and U2 categories were found in body weight, height at withers, chest circumference, body length, and scrotal circumference. Most TTS sold were white, horned, and had well-developed eye circumference. Pricing was primary based on external appearance rather than measurable traits. Further studies are recommended to explore pricing strategies based on body weight and to encourage the use of standardized livestock grouping by weight and appearance. Providing official health certificates may also enhance buyer trust and selling price.